Effects of sweet potato vine silage supplementation on meat quality, antioxidant capacity and immune function in finishing pigs. Issue 2 (6th June 2022) - Sun, Bo; Wang, Ruibo; Yue, Zhiyuan; Zheng, Hao; Zhou, Qinglong; Bao, Chunna; Shi, Baoming; Lv, Yinfeng; Shan, Anshan; Ma, Qingquan
Abstract: Sweet potato vine, the byproduct of sweet potato, has a high nutritional value. Silage is an effective solution for nutrient preservation. This article explored the effects of sweet potato vine silage (SPVS) supplementation on meat quality, antioxidant capacity and immune function in finishing pigs. One hundred and eighty finishing pigs (Berkshire × Licha Black) with a body weight of 74.54 ± 3.32 kg were randomly divided into three groups. The three groups were separately fed basal diet (Ctrl), Ctrl supplemented with 2.5% SPVS (LSPVS) or 5% SPVS (HSPVS) on a dry matter basis. Results showed that the eye muscle area in the LSPVS group was significantly increased. The carcass weight in the HSPVS was significantly reduced compared with Ctrl. For the meat quality, only cooking loss in both HSPVS and LSPVS was reduced while other indexes had no significant differences. For the antioxidant capacity, the hepatic level of glutathione (GSH) peroxidase (GSH‐PX) was significantly upregulated in LSPVS but downregulated in HSPVS. In the serum, HSPVS decreased GSH level and increased GSH‐PX level. HSPVS significantly reduced hepatic interleukin‐1β (IL‐1β) levels and LSPVS significantly reduced IL‐12 levels and increased IL‐8 and IL‐6 levels. Moreover, HSPVS and LSPVS promoted the secretion of immunoglobulin M (IgM) and IgG in the serum. Our data showed that low‐dose SPVS supplementation improved carcass traits and high‐dose SPVS supplementation increased immune function in finishing pigs, which provides a new alternative to improve animal health.